Methadone associated long term hearing loss and nephrotoxicity; a case report and literature review - Saeedeh Ghasemi; Shadi Izadpanahi; Mohammad Ali Yaghoubi; Jeffrey Brent; Omid Mehrpour (BMC, 2019)
Abstract Background Methadone is a long-acting opioid receptor agonist. Reported adverse effects of methadone include constipation, respiratory depression, dizziness, nausea, vomiting, itching, sweating, rhabdomyolysis, QT prolongation, and orthostatic hypotension. Hearing loss has been rarely reported following methadone use, and when reported, long term follow-up is rare. Herein we report a case of methadone poisoning with rhabdomyolysis, acute kidney injury, and persistent hearing loss documented by a 2 year follow up. Case presentation The patient was a 34 years old male who presented with a reduced level of consciousness and acute hearing loss after suicidal ingestion of 40 mg of methadone while experiencing family-related stresses. He had no prior history of methadone use, abuse, or addiction. Initial laboratory testing was significant for a serum creatinine concentration of 4.1 mg/dl, a mixed metabolic and respiratory acidosis, thrombocytopenia, abnormal hepatic transaminases, and coagulation tests. The patient then developed severe rhabdomyolysis. Also, audiometry showed a bilateral sensorineural hearing loss. The patient required hemodialysis for 11 days while his metabolic abnormalities gradually resolved. However, his hearing loss was persistent, as demonstrated by 2 years of follow up. Conclusion Our patient simultaneously had kidney failure, rhabdomyolysis, and permanent hearing loss following methadone poisoning. Although rare, ototoxicity and permanent hearing loss may happen in cases of methadone poisoning. While opioid-induced hearing loss is uncommon, methadone toxicity should be taken into account for any previously healthy patient presenting with acute hearing loss with or without rhabdomyolysis.